Inovasi Pangan Lokal Khas Dou Mbojo (Chanos Chanos) Sebagai Complementer Food Pencegah Stunting - Sri Yanti; Mardian Andriani; Mirham Nurul Hairunis (JUSTER : Jurnal Sains dan Terapan, 2024)
The 2025 global nutrition target aims to reduce stunting, focusing on accelerating efforts in implementing local food innovation. In the Bima area, milkfish (Chanos Chanos) has emerged as a strategic commodity due to its potential to meet children's nutritional needs affordably. However, the fish's many spines pose a choking hazard, especially for children. To address this, an innovative solution has been proposed: processing milkfish into complementary food into milkfish salome. This research sought to determine the acceptability of Salome among children aged 2-5 years. Using a Completely Randomized Design (CRD) with three serving types (soup, grilled, and fried Salome) and purposive sampling, the study employed questionnaires and data analysis through the Anova Analysis and the Games-Howell advanced test. The organoleptic test results indicated that fried Salome was the preferred variant, with subsequent tests revealing significant differences in aroma, texture, taste, and colour among original, fried, and grilled salome. Notably, milkfish Salome offers 6.4 grams of protein, 1.2 grams of fat, and 10.5 grams of carbohydrates per 100-gram serving.